노면결빙 및 안개 데이터 기반 도로 위험도 평가 - 양충헌(Choongheon Yang); 김진국(Jinguk Kim) (디지털콘텐츠학회논문지, 2021)
도로는 대표적인 기상조건인 강설·강우·안개에 취약한 특성을 가지고 있다. 이는 도로 교통류의 안정성을 현격하게 감소시켜, 교통사고 위험 가능성을 높인다. 도로 주행 중 운전자가 경험하는 다양한 기상조건은 필연적인 것으로, 기상으로 인해 열악해진 도로주행환경에 대한 위험 정도를 파악하는 것이 매우 중요하다. 본 연구에서 사업용 차량에 장착된 영상센서 및 DTG(Digital Tacho Graph)를 활용하여 도로 상의 안개 및 노면결빙 데이터를 수집·처리하고, 수집된 데이터와 도로속성데이터를 융·복합할 수 있는 알고리즘과 시스템 개발을 통해 새로운 형태의 도로위험정보를 제공할 수 있는 방법론을 정립하였다. 결과적으로 이러한 방법론을 테스트베드에 적용하여 특정구간에 대한 도로 위험도를 평가하고 시사점을 도출하였다. Road tends to be vulnerable to snowfall, rainfall, and fog which are typical weather conditions. This may significantly reduce the stability of traffic flow and increase the likelihood of traffic accidents. Various weather conditions experienced by drivers while driving on the road are inevitable, and thus it is very important to grasp the degree of risk that has become inferior due to the weather. In this study, fog and road freezing data on the road are collected and processed using the image sensor and DTG (Digital Tacho Graph) installed in commercial vehicles. The methodology developed here can provide new types of road hazard information has been established through the development of algorithms and the relevant system that can combine the collected data and road inventory data. As a result, this methodology was applied to the testbed to evaluate the road risk for a specific roadway section. KCI Citation Count: 0